2005
DOI: 10.1111/j.1460-9568.2005.04046.x
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral optic nerve crush induces bilateral retinal glial cell proliferation

Abstract: The post-injury responses of retinal ganglion cells elicit a number of glial reactions which have not been completely understood. The bilateral pattern of non-neuronal retinal cell proliferation was examined in association with the differential fates of unilaterally injured adult retinal ganglion cells by means of bromodeoxyuridine (BrdU) immunocytochemistry. Lateralization of the glioproliferative events was studied by analysing both the experimental and the uninjured contralateral as well as matched retinas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 25 publications
(35 reference statements)
5
54
0
3
Order By: Relevance
“…If we used the protocol like Piri et al by comparing the OH eye with the control eye, our conclusion would also indicate that OH caused down regulation of crystallins in the OH eye. There are increasing lines of evidence that unilateral nerve injury evokes contralateral responses [Bodeutsch et al, 1999;Kleinschnitz et al, 2005;Panagis et al, 2005]. Induction of OH in the right eyes may also cause stress in the contra-lateral left control eyes; and therefore, the use of the contralateral retina as a control in experimental glaucoma study is questionable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…If we used the protocol like Piri et al by comparing the OH eye with the control eye, our conclusion would also indicate that OH caused down regulation of crystallins in the OH eye. There are increasing lines of evidence that unilateral nerve injury evokes contralateral responses [Bodeutsch et al, 1999;Kleinschnitz et al, 2005;Panagis et al, 2005]. Induction of OH in the right eyes may also cause stress in the contra-lateral left control eyes; and therefore, the use of the contralateral retina as a control in experimental glaucoma study is questionable.…”
Section: Discussionmentioning
confidence: 98%
“…The average density of RGCs was calculated for the entire retina. Changes in the density of RGCs were expressed as a percentage loss of RGCs by comparing the laser treated right eye and normal control eye [Panagis et al, 2005]:…”
Section: Counting Of Rgcs and Statistical Analysismentioning
confidence: 99%
“…Gln. * P \ 0.05, *** P \ 0.001 relative to the Con group the right eyes were not used as controls because insulting unilateral optic nerve may affect the morphology and metabolism of the contralateral optic nerve and retina [26].…”
Section: Concentrations Of Retinal Metabolites Measured By Ex Vivo 1 mentioning
confidence: 99%
“…If recognition of Ag of retinal origin leading to development of T reg involves local collection of Ag and its transfer to peripheral lymphoid tissues for presentation to CD4 T cells, then altering this process could affect the periph- eral development of T reg activity. Extraocular injury (crush) to the optic nerve is well known to induce apoptosis in retinal ganglion cells and lead to retinal micro glial and astroglial activation [16] . In related studies, we have found that a significant number of cells with a dendritic cell phenotype (CD11c+I-A k +) appear in the retina within a few days of an optic nerve crush (unpublished results).…”
Section: Retinal Injury Alters the Regulatory Responsementioning
confidence: 99%